Using drone imagery to upscale estimates of water capacity in tank bromeliads on steep neotropical inselbergs - Lehmann, Jan R. K.; Prior, Milan D.; Paula, Luiza F. A.; Azevedo, Luísa; Porembski, Stefan; Buttschardt, Tillmann K.; Solar, Ricardo (Austral ecology, 2022)
A substantial fraction of stored freshwater available on neotropical inselbergs is impounded within the rosettes of bromeliads. Their high water retention capacity can potentially have an outcome on the inselberg community as well as on the surrounding environment. However, there are no studies measuring and extrapolating the water retention capacity of bromeliads from single observations to larger spatial scales. Using simple drone‐based imagery, we were able to calculate and upscale the water tank capacity of Alcantarea distractila, a bromeliad genus which is widespread on inselbergs in Southeastern Brazil. Our results provide a firstarge scale quantification of the estimated availability of water tank reservoir of inselbergs, which highlights the potential provisional ecosystem service delivered by bromeliad species. Resumo Uma parte substancial da água doce armazenada disponível em inselbergs neotropicais é capturada dentro das rosetas das bromélias. A alta capacidade de retenção de água destas plantas pode, potencialmente, ter efeitos na comunidade dos inselbergs, bem como no ambiente ao redor. Entretanto, não há estudos medindo e extrapolando a capacidade de retenção de água, desde as bromélias individuais até medidas em escalas espaciais maiores. Usando fotografias simples obtidas por drones, nós conseguimos calcular, também estimando para escalas espaciais maiores, a capacidade do tanque de água de Alcantarea distractila, um gênero de bromélia dominante nos inselbergs do sudeste Brasil. Nossos resultados fornecem uma primeira quantificação da disponibilidade estimada de água apreendida nos tanques de bromélias de inselbergs, o que destaca o potencial deste serviço ecossistêmico de provisão prestado pelas bromélias. Using simple drone‐based imagery, we were able to calculate and upscale the water tank capacity of Alcantarea distractila, a bromeliad genus which is widespread on inselbergs in Southeastern Brazil. Our results provide a first large‐scale quantification of the estimated availability of water tank reservoir of inselberg, which highlights the potential provisional ecosystem service delivered by bromeliad species.